2022
DOI: 10.1007/s11227-022-04631-z
|View full text |Cite
|
Sign up to set email alerts
|

Explainable artificial intelligence approach in combating real-time surveillance of COVID19 pandemic from CT scan and X-ray images using ensemble model

Abstract: Population size has made disease monitoring a major concern in the healthcare system, due to which auto-detection has become a top priority. Intelligent disease detection frameworks enable doctors to recognize illnesses, provide stable and accurate results, and lower mortality rates. An acute and severe disease known as Coronavirus (COVID19) has suddenly become a global health crisis. The fastest way to avoid the spreading of Covid19 is to implement an automated detection approach. In this study, an explainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A confusion matrix is used to demonstrate the corresponding results. It is a tool to show correct and incorrect classification results to explain which classes testing images are miss-classified [38].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…A confusion matrix is used to demonstrate the corresponding results. It is a tool to show correct and incorrect classification results to explain which classes testing images are miss-classified [38].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Ullah F. et.al. [40] contributed in detection and classification Covid-19 in CT and X-ray images. Ravi V. et.al.…”
Section: Research Purposes and Objectivesmentioning
confidence: 99%
“…One article collected data From D. S. Kermany, et al, "Identifying medical diagnoses and treatable diseases by image-based deep learning", J. P. Cohen, P. Morrison, and L. Dao, "Covid-19 image data collection" [45]. Another one from Git hub, Italian Society of Medical and Interventional Radiology, Radiological Society of North America (RSNA), Radiopaedia, and SIRM) and Kaggle repository [52].…”
Section: Exploration Of Used Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Even though many studies [ 14 , 15 , 16 , 17 , 18 , 19 ] have produced information regarding COVID-19 by using the concept of big data, machine learning and artificial intelligence, studies related to the prediction of mortality using different AI-driven models are rare globally and in the region. Based on our search, no study has reported on the use of AI-driven ensemble modelling to predict mortality due to COVID-19 in the region.…”
Section: Introductionmentioning
confidence: 99%